Application of the Kerthi Bali Economy in a Web-Based Geospatial Visualization Information System - Karyada, I Putu Ferry; Sanjaya, Kadek Oky; Arthadana, Made Gede; Paramita, I Gusti Agung; Mahayasa, I Gede Aryana (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Traditional village is a unit of customary law community in Bali which has territory, position, original structure, traditional rights, own assets, traditions, and social manners of community life from generation to generation. One of the values ​​of local wisdom that can be implemented in economic activities is Sad Kerthi, namely the six main sources of welfare/happiness of human life. The Kerthi Bali Economy is an economy to realize an Independent Bali in the Economic Sector, built and developed based on the values ​​of Sad Kerthi's philosophy. Because the principle of Kerthi Bali Economics is a new concept, the researcher analyzes the contents and phenomena described in the Kerthi Bali Economics book and is associated with other economics references. At this stage will produce an indicator in measuring the economic principles of Kerthi Bali. There are 11 economic principles of Kerthi Bali that are harmonious with nature, culture and people. The development model used by the researcher uses the Waterfall Model. In this study, researchers used several stages in the waterfall model, including requirements, design, implementation, verification, and maintenance. The system design uses MySQL as the database as well as PHP and HTML for basic programming. This research succeeded in developing the Application of the Kerthi Bali Economy in a Web-Based Geospatial Visualization Information System. Testing the system using the Black Box Testing method, which produces all the pages tested in accordance with the expected results.